A Poetic Inquiry Into (Re)Connecting With the Language of the Land: Walking with dįį ndéh - Lafferty, Anita (Journal of the Canadian Association for Curriculum Studies, 2022)
In this article, I strive to move beyond the pervasiveness of colonial ideologies and intellect, decolonizing my experiences by learning through the physical act of being and doing on the Land, while provocatively listening to the silences. It is through the exploration and ingenuity of poetry that the language and knowledge of my ancestors evolved. Weaving in and out of poetic and storied landscapes, I engage with learning from and with dįį ndéh as the medicine stories of my matriarchs begin to unfold.